Learning to Coordinate Efficiently through Multiagent Soft Q-Learning in the presence of Game-Theoretic Pathologies - Danisa, Siphelele (Department of Mathematics and Applied Mathematics, 2023)
In this work we investigate the convergence of multiagent soft Q-learning in continuous games where learning is most likely to be affected by relative overgeneralisation. While this will occur more often in multiagent independent learner problems, it is present in joint-learner problems when information is not used efficiently in the learning process. We first investigate the effect of different samplers and modern strategies of training and evaluating energy-based models on learning to get a sense of whether the pitfall is due to sampling inefficiencies or underlying assumptions of the multiagent soft Q-learning extension (MASQL). We use the word sampler to refer to mechanisms that allow one to get samples from a given (target) distribution. After having understood this pitfall better, we develop opponent modelling approaches with mutual information regularisation. We find that while the former (the use of efficient samplers) is not as helpful as one would wish, the latter (opponent modelling with mutual information regularisation) offers new insights into the required mechanism to solve our problem. The domain in which we work is called the Max of Two Quadratics differential game where two agents need to coordinate in a non-convex landscape, and where learning is impacted by the mentioned pathology, relative overgeneralisation. We close this research investigation by offering a principled prescription on how to best extend single-agent energy-based approaches to multiple agents, which is a novel direction.